AN ARCHITECTURAL ADAPTATION STRATEGY FOR THE DYNAMICS OF THE KAHAYAN RIVER’S WATER LEVEL AT KAMPUNG PAHANDUT, PALANGKA RAYA CITY - Alifi Diptya Nidikara; Giosia Pele Widjaja (Riset Arsitektur (RISA), 2017)
Abstract- Kalimantan (Borneo) is famous as the island of a Pulau Seribu due to the large number of rivers that run across its cities. One of the longest is the Kahayan river that flows through the city of Palangka Raya. The river as an important aspect in Kalimantan people’s life has made it the starting point for the embryo of a city in the form of river side dwellings that keeps on developing amidst the dynamics of the Kahayan river that undergoes a high degree of change in terms of water level during the dry and rainy seasons. The issue that arises is the addition and loss of space due to the changes of the river water level. The purpose of this research is to describe the adaptation strategies used by the writer in Kampung Pahandut that is unique when compared other kampongs (villages) due to its condition of having dry and flooded streets in the dwelling area. This research is qualitative in nature, employing the narrative descriptive method. The data collection technique uses purposive sampling to collect the physical and activity data. The physical and activity data were gained through a survey of the research object as well as picture taking, field observation, as well as the medium ofinterviews conducted with the Kampung Pahandut villagers. The data was then processed by classifying the numerous changes that had happened in both physical and activity-related terms as well as analyzing and concluding the adaptation strategies. It was found that in Kampung Pahandut there were both physical and activity-related changes as efforts to accommodate its people to enable them to survive the dry and flooding condition due to the changes of the river water level. Within these efforts there was also architectural adaptation based on the study consisting of three adaptation strategies, namely: being adjustable, refittable, and movable. Keywords: architectural adaptation, changes in water level, Kahayan River, Kampung Pahandut